The Effect of Investment Toward Economic Growth in The Local Economy - Saadah Yuliana; Abdul Bashir; Siti Rohima (Jurnal Ekonomi dan Studi Pembangunan, 2019)
This study to analyze the role of investment such as total foreign direct investment and domestic direct investment, inflation, and road infrastructure to the economic growth of South Sumatera Province, Indonesia. The data used is time series data from 2007-2015, the scope of this study is 15 districts/city in South Sumatera Province, which is sourced from the publication of Central Bureau of Statistics (BPS) and the publication of the Investment Coordinating Board (BKPM) South Sumatra Province. The analysis method in this study is quantitative analysis using data panel multiple regression model. The finding of this study that investment, inflation, and road infrastructure development jointly has positive and significant effect on the economic growth. Meanwhile, partially indicating that investment and road infrastructure have positive and significant impact to economic growth, while inflation has positive sign but insignificant effect on economic growth of South Sumatera Province